Employment Negotiation Behaviours of Canadian Academic Librarians: An Exploratory Study - Cardozo, Paula; Scott, Emma (Partnership, 2021)
While a small number of studies have investigated salary negotiation in librarianship, none have focused on Canadian academic libraries. What are the motivations and barriers that impact employment-offer negotiation? When Canadian librarians negotiate, what subjects are discussed, and do they feel they were successful? This preliminary report is a descriptive summary on the results of a survey we conducted to explore the negotiation propensity and perceptions of Canadian academic librarians when presented with their most recent offer of employment. A better understanding of this topic may encourage negotiation conversations and empower librarians in future employment offer negotiations to improve salaries and working conditions.